Durum wheat varieties in N‐deficient environments and organic farming: a comparison of yield, quality and stability performances. Issue 3 (28th March 2013) - Stagnari, Fabio; Onofri, Andrea; Codianni, Pasquale; Pisante, Michele; Becker, H.
Abstract Stability and reliability of yield and quality for 15 durum wheat genotypes (old and modern) were evaluated in a 5‐year experiment (southern Italy) in organic farming. Genotypes were grown at two N levels (0 and 80 kg/ha), with the aim of evaluating 'genotype × environment' (GE) interactions and their role on genotype selection in N‐limited environments. Several approaches to stability were used, within the frame of mixed models and additive main effects and multiplicative interaction analysis, and their validity in stressful conditions and organic farming was discussed. Especially for protein and gluten content, results indicate high environmental variability and the presence of crossover 'N × environment' interactions, which supports the need for specific breeding programmes in N‐deficient environments. The average response was strongly affected by N availability (on average, yield was 2.95 and 3.42 t/ha, protein content was 11.6% and 12.85%, gluten content was 8.55% and 9.92%, respectively, at 0 and 80 kg N/ha), and few genotypes gave high yield and quality at both fertilization levels. Only 'Gargano' and 'Fortore' showed a good inter‐year stability at both N levels. The old cultivars gave minimal responsiveness to increased N input, but gave good results in limiting conditions, indicating that they may play a role in organic farming.